Regression dependence - Siburg, Karl F.; Stoimenov, Pavel A. (Technische Universität Dortmund, 2009)
This paper presents a framework for comparing bivariate distributions according to their degree of regression dependence. We introduce the general concept of a regression dependence order (RDO) and provide two examples of RDOs. In addition, we define a new nonparametric measure of regression dependence and study its properties. Beside being monotone in the new RDOs, the measure takes on its extreme values precisely at independence and almost sure functional dependence, respectively. Finally, a consistent nonparametric estimator of the new measure is constructed.
Discussion Paper / SFB 823; 10/2009
Keywords: 310; 330; 620